Clinical tests and magnetic resonance imaging have limited diagnostic value for triangular fibrocartilaginous complex lesions - Schmauß, Daniel; Pöhlmann, Sebastian; Lohmeyer, Jörn Andreas; Germann, Günter; Bickert, Berthold; Megerle, Kai Oliver (Archives of orthopaedic and trauma surgery, 2016)
The diagnostic value of clinical tests and magnetic resonance (MR) imaging for the investigation of triangular fibrocartilaginous complex (TFCC) lesions is not clear due to a lack of clinical data.
Gesehen am 15.05.2020